The role of macrophage metabolic reprogramming in myocardial infarction - ZOU Zicong; GU Muyang; CHENG Xiang (Guangxi Yike Daxue xuebao)
Myocardial infarction (MI) is one of the major cardiovascular diseases that threaten human health and the post-MI inflammation affects its progression and prognosis. Although the inflammatory response is necessary for tissue repair, persistent inflammatory activation exacerbates the process of cardiac remodeling and serves as an important factor of heart failure after MI. Macrophages, as one of the important innate immune cells, play a crucial role in the immune response, necrotic tissue clearance, and tissue repair after MI. While adapting to the post-MI microenvironment, responding to activation signals, and exerting functions, the metabolic phenotype of macrophages undergo significant changes. The metabolic reprogramming mechanism of macrophages in response to microenvironmental changes after MI is also the basis for their phenotypic and functional plasticity, allowing them to play different roles at various stages after MI. This review summarizes the phenomenon of metabolic reprogramming in macrophages after MI and its impact on the regulation of inflammation and tissue repair after MI, providing more perspectives and scientific evidence for the development of macrophage-targeted therapeutic strategies.